Arthur Szyk preserved : institutional collections of original art : the essential compendium of publicly held works - Szyk, Arthur (Historicana, 2023)
Arthur Szyk (pronounced "Shick") was born in Lodz, Poland, in 1894 and died in New Canaan, Connecticut, in 1951. He was considered the greatest miniaturist and painter-illuminator of his era, and the leading political artist in America during World War II. He was internationally recognized and celebrated, and his works of art continue to be exhibited worldwide. This catalogue of institutional holdings of Arthur Szyk's art was created to provide the best jumping off point for those interested in surveying his originals for the purpose of research, scholarship, and curatorial possibilities. 'Arthur Szyk Preserved' illustrates where Szyk's work can be found today. Ultimately, this catalogue recognizes and celebrates the public institutions that serve as vital caretakers of Arthur Szyk's art and legacy. It is hoped that this publication will encourage them to more fully promote public awareness of Szyk's art and the breadth and beauty of his works in multiple and creative ways